2018
DOI: 10.1175/waf-d-18-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Further Improvements to the Statistical Hurricane Intensity Prediction Scheme Using Tropical Cyclone Rainfall and Structural Features

Abstract: The Statistical Hurricane Intensity Prediction Scheme (SHIPS) is a multiple regression model for forecasting tropical cyclone (TC) intensity [both central pressure (Pmin) and maximum wind speed (Vmax)]. To further improve the accuracy of the Japan Meteorological Agency version of SHIPS, five new predictors associated with TC rainfall and structural features were incorporated into the scheme. Four of the five predictors were primarily derived from the hourly Global Satellite Mapping of Precipitation (GSMaP) rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…However, as noted above, this type of a persistence forecast can lead to large errors, such as at the onset or ending of RI and RW. While the importance of keeping DELV is also supported by its use in both the OCD5 and SHIPS models (Knaff et al 2003;DeMaria and Kaplan 1994;Shimada et al 2018), it is worth investigating whether other information can be leveraged so that the model has a priori knowledge of when a persistence forecast may not be warranted. One method to do this would be to introduce a variable such as the difference between the intensity of the storm and its maximum potential intensity, as is done in the LGEM model (DeMaria 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, as noted above, this type of a persistence forecast can lead to large errors, such as at the onset or ending of RI and RW. While the importance of keeping DELV is also supported by its use in both the OCD5 and SHIPS models (Knaff et al 2003;DeMaria and Kaplan 1994;Shimada et al 2018), it is worth investigating whether other information can be leveraged so that the model has a priori knowledge of when a persistence forecast may not be warranted. One method to do this would be to introduce a variable such as the difference between the intensity of the storm and its maximum potential intensity, as is done in the LGEM model (DeMaria 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will include adding new predictors to further improve the prediction accuracy of SHIPS. For example, Shimada et al (2018) demonstrated improved accuracy by using a microwave satellite-derived rainfall dataset from the Global Satellite Mapping of Precipitation (GSMaP, Kubota et al 2007;Aonashi et al 2009). Another future study will include the use of the JMA official TC track forecasts instead of JMA/GSM track predictions when calculating environmental predictors such as the ocean heat content and/or vertical wind shear.…”
Section: Discussionmentioning
confidence: 99%
“…where s ′ ( • ) is the derivative of s( • ) and diag( • ) denotes extending a vector to a diagonal matrix. Equations (6) and 7indicate that the outputs h t at time t are related to those at the previous time (h k ), while W can directly describe such relationship. The solutions for U and V are similar to (6) and 7.…”
Section: Fig 1 Illustration For Proposed Modelmentioning
confidence: 99%
“…Equations (6) and 7indicate that the outputs h t at time t are related to those at the previous time (h k ), while W can directly describe such relationship. The solutions for U and V are similar to (6) and 7. Once the parameter set u is determined, our prediction model has been established.…”
Section: Fig 1 Illustration For Proposed Modelmentioning
confidence: 99%